2022
DOI: 10.1109/access.2022.3187528
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Based Prediction of Reference Evapotranspiration (ET0) Using IoT

Abstract: Accurate estimation of Reference Evapotranspiration (ET 0 ) is important for efficient management and conservation of irrigation water. Existing methods of ET 0 rate determination are complex for application at the farmer level. Apart from standard methods of ET 0 determination, many data-driven soft computing approaches were also proposed to determine the ET 0 with limited data set. We proposed a temperature and humidity-based ML approach for ET 0 rate determination on directly sensed environmental conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 48 publications
0
8
1
Order By: Relevance
“…While Tr et al [16] achieved a lower RMSE (0.016), their results may not be directly comparable due to potentially limited data scope or specific application. Compared to other studies (Hill et al [9], Hu et al [12], Dong et al [18]), our approach demonstrates significantly lower and more consistent RMSE and MAE values across a wider range, which suggests greater generalizability and accuracy. This highlights the effectiveness of our method in precisely estimating EV T 0 for various agricultural applications.…”
Section: Results Comparisoncontrasting
confidence: 46%
“…While Tr et al [16] achieved a lower RMSE (0.016), their results may not be directly comparable due to potentially limited data scope or specific application. Compared to other studies (Hill et al [9], Hu et al [12], Dong et al [18]), our approach demonstrates significantly lower and more consistent RMSE and MAE values across a wider range, which suggests greater generalizability and accuracy. This highlights the effectiveness of our method in precisely estimating EV T 0 for various agricultural applications.…”
Section: Results Comparisoncontrasting
confidence: 46%
“…Different sensor nodes, network layer protocols, cloud services and ML algorithms developed for smart agriculture applications viz. irrigation monitoring ( [1], [26], [27], [34], [43], [44]), production process management ( [28], [29], [41]), plant growth and disease monitoring ( [30], [31], [32], [38], [39], [42]) and precision agriculture ( [33], [34], [40]) are considered in Table III.…”
Section: Review Discussionmentioning
confidence: 99%
“…We assess the accuracy of three machine learning techniques for determining ET0: Gaussian Naïve Bays (GNB), K-nearest neighbor (KNN), support vector machine (SVM), and artificial neural network (ANN). It has been demonstrated that KNN is more accurate than SVM and GNB models, with 92% accuracy, high precision, recall, and f-measure [32] 6. LR, LDA, KNN, CART, NB, and SVM The paper describes an intelligent system for the Internet of Things, LoRa-based wireless sensor networks, and machine learning for scheduling and monitoring precise irrigation.…”
Section: Architecture Of the Proposed System And Working Principalsmentioning
confidence: 99%